The Role of Humour in the Comics (Eurasian Journal of Learning and Academic Teaching, 2022)
Humor is one of the national qualities of our nation, which testifies to their high talent, sharp intelligence, graceful nature, cheerfulness, penchant for humor. By the oral creativity of our people, great attention is paid to the pilgrimage, which is clearly visible in historical sources